The Digital Shift in Corporate Social Responsibility: Analysing ‎The Evolution of CSR Communication - Ashitha, T; Satheesh , Dr. E. K. (International Journal of Accounting and Economics Studies, 2025)
The body of knowledge on corporate social responsibility (CSR) has expanded rapidly but ‎remains dispersed across journals and disciplines. This paper conducts a bibliometric analysis ‎and systematic literature review of studies on CSR and its Digital Communication (DCSR)/ ‎Digital CSR, using PRISMA for the systematic collection of papers from Scopus and Web of ‎Science. CSR is vital for ethical business practices, yet a lack of awareness often excludes ‎beneficiaries. Results reveal steady growth in Digital CSR research, primarily from developed ‎countries like the U.S. and U.K., while developing and emerging economies are ‎underexplored. Citation, co-authorship, and co-occurrence mapping highlight relationships ‎among journals, nations, and articles. Sustainable practices are a focus in developed nations, ‎emphasizing the need for adoption in emerging regions. These findings guide CSR practitioners ‎and policymakers in developing impactful communication strategies‎.